Larangan Penguasaan Tanah Oleh Wna Melalui Perjanjian Nominee - Kadek Ramdhana Wija Dharma; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
A nominee agreement is an agreement made between a person who according to law cannot be the subject of certain land rights (property rights), in this case a foreigner and an Indonesian citizen, with the intention that the foreigner can control (own) the land with the right of ownership legally. de facto, but legally-formally (de jure) the land with the right of ownership is in the name of an Indonesian citizen. Foreign nationals who control land owned by Indonesian citizens by entering into a nominee agreement. This research was conducted to examine the form of prohibition of land tenure by foreigners through the Nominee Agreement. The research method used is an empirical method with a statutory regulatory approach and conceptual approach. This study uses primary legal materials and secondary legal materials. data collection techniques by collecting, studying, exploring and reviewing documents in depth relating to the problems studied. The data collected were analyzed using qualitative methods. The results of this study indicate that the validity of the nominee agreement and the legal position of foreign citizens in land tenure through the nominee agreement. The legal force of a nominee agreement can be seen from the fulfillment or not of the legal requirements of an agreement as specified in Article 1320 of the Civil Code and good faith at the stage of contract formation, negotiation and signing of the nominee agreement